Modernization of Asian Theatres
XIV, 262 p. 33 illus., 9 illus. in color.
Keywords: This volume focuses on the theatre history of Asian countries, and discusses the specific context of theatre modernization in Asia. While Asian theatre is one of the primary interests within theatre scholarship in the world today, knowledge of Asian theatre history is very limited and often surprisingly incorrect. Therefore, this volume addresses a major gap in contemporary theatre studies. The volume discusses the conflict between tradition and modernity in theatre, suggesting that the problems of modernity are closely related to the idea of tradition. Although Asian countries preserved the traditional form and values of their respective theatres, they had to also confront the newly introduced values or mechanisms of European modernity. Several papers in this volume therefore provide critical surveys of the history of theatre modernization in Asian countries or regions—Japan, Korea, Taiwan, Hong Kong, India Malaysia, Singapore, and Uyghur. Other papers focus on specific case studies of the history of modernization, discussing contemporary Taiwanese performances, translations of modern French comedy into Chinese, the modernization of Chinese Xiqu, modern Okinawan plays, Malaysian traditional performances, Korean national theatre, and Japanese plays during World War II. Renowned academics and theatre critics have contributed to this volume, making it a valuable resource for researchers and students of theatre studies, literature, and cultural studies.